2005
DOI: 10.1177/014556130508400112
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Middle Ear Trauma: A Report of 2 Cases

Abstract: Penetrating middle ear injury can result in hearing loss, vertigo, andfacial nerve injury. We describe the cases of 2 children with penetrating trauma to the right ear that resulted in ossicular chain disrupt ion; one injury was caused by cotton-tipped swabs and the other by a wooden matchstick. Symptoms in both children included hearing loss and otalgia ; in addition, one child experienced ataxia and the other vertigo. Physical examination in both cases revealed a pelf oration in the posterosuperior quadrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Penetration of the TM by objects may lead to ossicular chain disruptions in the middle ear. 4 It may also be complicated with suppurative middle ear disease if the penetrating object harbour some infective organisms as seen in some of our patients. Orji and Agu reported that healing of TTMP was delayed by middle-ear infection and confirmed that penetrating injuries sustained through the ear canal was an important risk factor in predicting non-healing of TTMP.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Penetration of the TM by objects may lead to ossicular chain disruptions in the middle ear. 4 It may also be complicated with suppurative middle ear disease if the penetrating object harbour some infective organisms as seen in some of our patients. Orji and Agu reported that healing of TTMP was delayed by middle-ear infection and confirmed that penetrating injuries sustained through the ear canal was an important risk factor in predicting non-healing of TTMP.…”
Section: Discussionmentioning
confidence: 71%
“…The TM injury can predispose to middle ear infection which has grave consequences including facial nerve paralysis, formation of cholesteatoma, perilymph fistula, intracranial infections and may require ear and intracranial exploration. 4 Significant morbidity or mortality can occur when traumatic ear injuries are associated with damage to contiguous facial structures and the brain. Effective management is expedient while prevention and reduction of complications must be given utmost attention to achieve a good outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies for traumatic conductive hearing loss (CHL) are not as clear. Reports include immediate exploration and repair within days of traumatic injury (3,4), exploration and repair after 6 to 7 weeks for suspected traumatic ossicular lesions (5), or exploration and repair after 3 months (1,6,7). This variability may be due to the lack of data demonstrating the natural history of traumatic CHL.…”
mentioning
confidence: 99%
“…Previous studies have documented delayed treatment for severe CTA injuries, such as TMP, ossicular dislocation (joints between malleus-incus-stapes, or stapes footplate subluxation), hearing loss (conductive, sensorineural, or mixed), perilymphatic fistula, and facial nerve paralysis. 2,20 Smith et al reported a 7.4% rate of delayed surgical tympanic membrane repair after CTA injury. 2 In that study, TMP was seen in nearly 25% of cases, and foreign body sensation was the most common reason for ED visits.…”
Section: Discussionmentioning
confidence: 99%